The response of Islamic institutions and organizations to terrorism - Alispahić, Bakir; Halilović - Kibrić, Nerma (Technium Social Sciences Journal, 2021)
Every day, the citizens from all over the world witness numerous global changes at all levels of human life - from the politics, economy, culture, education, development of new media, universal human values, to the emergence of new forms of struggle for some of the goals that people and groups strive to achieve on global level. Terrorism as the greatest threat of today for all the world countries, has become one of the biggest security problems. The modern world has not yet found an adequate response to terrorism. This paper discusses the response to terrorism by the Islamic world i.e. some of the most important Islamic institutions and organizations in the world, in particular, the views of the Organization for Islamic Cooperation, the Academy for Islamic Research at Al-Azhar University, and the International Islamic Fiqh Academy.